Organised food crime: an analysis of the involvements of organised crime groups in the food sector in England and Italy - Rizzuti, Alice (Crime, law, and social change, 2022)
The food sector is subject to illegal practices of various types such as adulteration or exploitation of labour. In the media and public discourse, this phenomenon is often associated to activities by organised crime groups. Drawing on a socio-legal empirical study on the perception and conceptualisation of food crime in English and Italian public institutions, this paper unpacks the involvement of organised crime and mafia-type actors in the food sector. Considering data collected through in-depth interviews with representatives of law enforcement and other public authorities, supported by documentary sources, this research points out that, from both an institutional perspective that narrowly conceptualises as food crime as food fraud, as well as from a wider perspective that addresses other practices happening in the food sector, organised crime is involved in food crime. By referring to the English and Italian cases, and by merging different bodies of literature, such as green criminology and enterprise theory, this article advocates for conceptual clarity when referring to the involvement of corporate crime, organised crime and mafia-type groups active in the food sector. In so doing, it presents and reflects upon ‘organised food crime’ as a new socio-legal category and highlights its policy outcomes.